The Influence of Leadership Style and Work Motivation on Job Satisfaction - Irwan Usman; Nurhaeda (Jurnal Economic Resource, 2021)
Objectively, this study was conducted to examine and examine the effect of leadership style and work motivation on job satisfaction. The object of the research is a member of the Polewali Mandar Police. The population in this study were all members of the Police at Polewali Mandar Police, amounting to 497 people. The number of samples in this study was determined using the slovin formula to obtain a total sample of 83 respondents. Data was collected by distributing questionnaires. The data in this study were analyzed using the SPSS tool with several stages of testing such as validity, reliability, normality testing, and hypothesis testing consisting of simultaneous tests, coefficient of determination tests, and partial tests. Simultaneously and partially, leadership style and work motivation affect job satisfaction. Leadership style has the most dominant influence on job satisfaction for members of the Polewali Mandar Police. The results of this study suggest that the leadership style applied to police members at POLRES Polewali Mandar is more emphasized on consistent leadership in using rewards to stimulate member performance and providing punishment for personnel who violate the rules. It would be better if leadership education or official training were given to the leaders in this unit to get closer personally to members of POLRI.